Sea‐slug invasion of the land. (17th June 2015) - Kano, Yasunori; Neusser, Timea P.; Fukumori, Hiroaki; Jörger, Katharina M.; Schrödl, Michael
<x xml:space="preserve">Abstract</x> Invasion of the land has been a considerable challenge for aquatic organismal lineages, primarily because of desiccation and lack of physical support in air. Gastropod molluscs are among the most successful animals in this habitat shift because of their hard exoskeleton, whereas land slugs, regarded as descendants of land snails, gradually lost their shells in sheltered, moist environments. We present solid evidence of terrestrial invasion by a lineage of sea slugs; this invasion is represented by a newly discovered species, Aiteng marefugitus (Panpulmonata: Acochlidia), from a humid tropical rainforest on a small island in the Republic of Palau, western Pacific. The slug lineage seems to have invaded the forest habitat directly from the upper littoral zone in the Cenozoic.